The Effect of Warm Water Foot Bath Therapy in Reducing Blood Pressure in Elderly People with Hypertension in Pandansari Village, Banyumas - Puput Yulianingrum; Wasis Eko Kurniawan (Viva Medika, 2024)
As a person ages, various types of changes and non-communicable diseases often occur due to decreased biological function due to the aging process. The disease that often occurs is hypertension. If not treated properly, hypertension will cause complications. Preventing hypertension can be done with non-pharmacological therapy, namely by soaking the feet in warm water. The aim of this study was to see whether there was an effect of soaking the feet in warm water on reducing blood pressure in people with hypertension. This research is qualitative research using the nursing process approach method. The subjects used were elderly people with hypertension problems in Pandansari Village, Kab. Banyumas. The research instrument used was the nursing care format. Research data collection techniques are observation, interviews, physical examination and documentation studies. Blood pressure measurements were taken after and before the feet were soaked. The results of implementing foot soak therapy using warm water on the elderly showed that the patient's blood pressure decreased from the first day of implementation to the third day of implementation, so it can be concluded that the technique of soaking feet in warm water was able to provide good results. Lowering blood pressure in the elderly.